2016
DOI: 10.1093/gji/ggw379
|View full text |Cite
|
Sign up to set email alerts
|

Accurate relative location estimates for the North Korean nuclear tests using empirical slowness corrections

Abstract: SUMMARYDeclared North Korean nuclear tests in 2006, 2009, 2013, and 2016 were observed seismically at regional and teleseismic distances. Waveform similarity allows the events to be located relatively with far greater accuracy than the absolute locations can be determined from seismic data alone. There is now significant redundancy in the data given the large number of regional and teleseismic stations that have recorded multiple events, and relative location estimates can be confirmed independently by perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
(27 reference statements)
5
22
0
Order By: Relevance
“…Based on the published estimates of burial depths in Table , we specify depths of 380 m for NK1, 600 m for NK2, 420 m for NK3, and 750 m for NK4, NK5, and NK6. These depths are generally consistent with absolute estimates from precise relative location estimates (e.g., Gibbons et al, ; Pasyanos & Myers, ), but significant uncertainty remains, and we will evaluate the effect of these choices. Filtered synthetics for a distance of 5,500 km are then constructed for the chosen source depth for a range of yield spanning the estimates in Table along with Futterman t* values from 0.4 to 1.3 s. While some paths likely have frequency‐dependent attenuation, Chaves et al () found that overall their waveform predictions of the NK6 event favored a constant‐ Q model.…”
Section: Four‐hertz Amplitude Modelingsupporting
confidence: 61%
See 1 more Smart Citation
“…Based on the published estimates of burial depths in Table , we specify depths of 380 m for NK1, 600 m for NK2, 420 m for NK3, and 750 m for NK4, NK5, and NK6. These depths are generally consistent with absolute estimates from precise relative location estimates (e.g., Gibbons et al, ; Pasyanos & Myers, ), but significant uncertainty remains, and we will evaluate the effect of these choices. Filtered synthetics for a distance of 5,500 km are then constructed for the chosen source depth for a range of yield spanning the estimates in Table along with Futterman t* values from 0.4 to 1.3 s. While some paths likely have frequency‐dependent attenuation, Chaves et al () found that overall their waveform predictions of the NK6 event favored a constant‐ Q model.…”
Section: Four‐hertz Amplitude Modelingsupporting
confidence: 61%
“…The events were readily detected and identified (e.g., Walter et al, ), in addition to being announced. Precise relative locations for the six explosions, with uncertainties on the order of a few hundred meters, have been determined by numerous seismic differential arrival time studies (e.g., Carluccio et al, ; Gibbons et al, , ; He et al, ; Myers et al, ; Murphy et al, ; Selby, ; Wang et al, ; Wen & Long, ; Yao et al, ; Zhang & Wen, ; Zhao et al, ; Zhao, Xie, He, et al, ). Absolute locations are much more difficult to resolve, and various strategies have been used to place the suite of precise relative locations in absolute position with respect to the source region topography, locations of tunnel portals, and/or deformation features on the surface inferred from InSAR or satellite photography (e.g., Murphy et al, ; Myers et al, ; Pabian & Coblentz, ; Pabian & Hecker, ; Patton & Pabian, ; Wei, ), with recent results having less than ~0.5‐km variations.…”
Section: Introductionmentioning
confidence: 99%
“…The direction of the steepest grade for the 200905 and 201302 events ranges between 130°N and 140°N which is also the direction of the largest amplitude ratio and phase shift Geophysical Research Letters 10.1002/2017GL074577 anomalies. Gibbons et al [2016] also attribute topographic effects to surprising differences with Pn waveform similarity across the dense network of Japan. There is no correspondence between the amplitude ratio or phase shift anomalies with the size of the isotropic component from the RMT which only differ between events by an average of ±8% (ranging between 66 and 81%).…”
Section: Discussionmentioning
confidence: 91%
“…If we used 0.9 threshold, only 2% would be removed. Table S1 in the supporting information lists the Bayesloc body wave, surface wave grid search, and Norwegian Seismic Array (NORSAR) body wave relative locations from Gibbons et al [2016]. Figure 2 shows the measured surface wave and the predicted δt computed from the best fit relative location obtained through the grid search.…”
Section: Relative Location Resultsmentioning
confidence: 99%
“…At most regional and teleseismic stations with data accessible, the frequency band with enough signal‐to‐noise ratios (SNR) for NKT2006 is quite narrow. Additionally, according to accurate relative location results (e.g., Gibbons et al, ), the distances between NKT2006 and other Korean nuclear tests are significantly larger than distances among the others, which would increases the scatter in the observed spectral ratios at different stations especially at high frequencies.…”
Section: Introductionmentioning
confidence: 99%